ANALISIS PENGARUH TOTAL ASSET TURNOVER, RETURN ON EQUITY, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2011 (Students' Journal of Economic and Management, 2014)
This research aims to analyze the influence of total asset turnover, return on equity, earning per share, and debt to equity ratio against to the stock price in Manufacture company in Indonesia Stock Exchange the period 2009-2011.The populations in this research are 145 manufacture companies which are enlisted in Indonesia Stock Exchange of 2009-2011. The data in this research are obtained from Indonesia Stock Exchange. The sample are chosen by purposive sampling method as much as 136 companies. The data testing technique are by using multiple linier regression analysis. The analysis result shows the variable that has positive influence and significant against to the stock price are earning per share variable and debt to equity ratio. However, total asset turnover variable and return on equity take negative effect and significant against to the stock price. Keywords: Total Asset Turnover (TATO), Return On Equity (ROE), Earning Per Share (EPS), and Debt To Equity Ratio (DER), Stock Price.